Primary Students’ Conceptions about Issues in Astrobiology - Skoumios, Michael; Tsitini, Sofia (Advances in Social Sciences Research Journal, 2015)
Although students’ conceptions about the natural world have been explored the research that studies the students’ conceptions of issues related to the universe and the existence of life on it is limited. The present study aims to investigate lower primary students’ conceptions on issues in Astrobiology. In particular, students’ conceptions about the origin of the universe, the existence of the elements used by life on Earth elsewhere in the universe, the existence of life on other planets, the existence of other objects similar to the Sun, the existence of planets not orbiting the Sun, the elements needed for life and the possibility of life in extreme temperatures, were investigated. A questionnaire which was designed to be elicited students’ conceptions was used as a research data collection tool. The questionnaire was given to 214 students aged 8 years old in Greece. Data analysis enabled the identification and registration of students’ conceptions. It was found that most students use conceptions on several issues of Astrobiology differ from the views of school science knowledge.